Interpreting disaster science, defining its objectives and range - TEKNŐS, László (Studia Universitatis Babeș-Bolyai Ambientum, 2023)
The article aims to define, interpret, and identify the aims of Disaster Science, and to delimit the individual components along the examination of its disciplinary nature. Definition of the concept of Disaster Science, delimitation of its individual components from its concept, and further terminological examination of related elements. On the one hand, this is conducted with the help of the Internet and the so-called keyword search method in the Google search engine, specifically by searching for definitions, then by collecting the individual publications and the relevant bodies and organisations, and analysing their use of terminology. The frequency of occurrence of disasters around the world is constantly increasing, their destructive effects can increasingly be felt. Their averting and elimination generally exceed the national level of protection, so the research results should be given priority. Among the conclusions of this publication stands the research priorities of Disaster Research having different disciplines, and due to its multi-, inter- and transdisciplinary nature, there is no unified consensus regarding the methodology and terms. The availability of literature of sociological origin is ensured, however, few works have been produced in Hungary on this topic, for instance, and even in the field of analysis of the effects of natural disasters. The Author analyses the elements of Disaster Science in an interdisciplinary manner, combining several disciplines, provides insight into Disaster Science and its research areas, and in terms of literary resources, the reader can get to know many, primarily international literature.